The effects of binge drinking on attention in young adults - Monds, Lauren A.; Singleton, Matthew R.; Russell, Alex M. T. (Frontiers in Psychology, 2023)
Alcohol binge drinking is highly prevalent among young adults. While research has established the neurotoxic effects of general alcohol consumption, binge drinking presents unique deleterious effects on the brain through the acute intoxication and withdrawal cycle.The detrimental impacts of binge drinking have been reported across a broad range of cognitive abilities in young adults, however, the research regarding its relationship to attention is mixed. This study investigates the relationship between binge drinking and attention performance in young adults. Moreover, there is evidence to suggest that males and females are uniquely impacted by the neurotoxic effects of binge drinking, so the present study tests the moderating role of sex, as well as the influence of earlier age of binge drinking onset. One-hundred and five university students were recruited for the study. After collecting socio-demographic, and alcohol use information, participants completed four cognitive tasks designed to measure the three attention networks according to the Attention Network Theory; alerting, orienting, and executive control. Linear hierarchical regressions were used to predict performance with binge drinking score, sex and age of first binge drinking session as predictors. Binge drinking, sex, and age of first binge drinking session did not predict attention impairment, nor did sex moderate the relationship, at least in the selected cognitive tasks. The tasks used to measure attention did not relate in the expected manner. While there were no differences in attention performance between those who binge drink and controls in this study, the relationship between binge drinking and attention impairments in young adults may be more nuanced and future research directions are suggested. Theoretical and practical implications of these findings are discussed.